Investigation on low cost capacitive flood sensor operation and optimization based on Arduino microcontroler: article / Siti Noor Azreen Asmadi - Asmadi, Siti Noor Azreen (2013)
Flash flood problems often occurred on urban area. In Kuala Lumpur, SMART tunnel is built to handle this problem. Using a same concept, a low cost capacitive flood sensor is developed to overcome this problem on certain area around Kuala Lumpur. The development of flood sensor is based on Arduino microcontroller which used CapacitiveSensor library to detect the flood water level. The flood sensor is constructed from copper media which is implemented on the FR-4 PCB. The sensitivity of the flood sensor is tested under two different methods which used a single and parallel-plate capacitor respectively. The relationship between flood sensor sensitivity with different resistance values, temperature, size and gap between plates is investigated. All measurements taken were in an arbitrary unit which indicated the capacitance of the sensor. From the investigation done on the capacitive flood sensor, it is described that the flood sensor is easy to implement, low cost and has a high sensitivity and reliability of the results.